The Phenomenon of Personal Burnout: Psychological Causes and Consequences in Professional Activity - Nishonova Farangiz (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the relationship between the rule of law and civil society, as well as the mechanisms of their interaction and mutual influence. The study analyzes the importance of democratic institutions, legal culture, public participation, and the protection of human rights in the formation of a modern legal state. Special attention is paid to the role of civil society institutions in strengthening legality, ensuring transparency in state governance, and protecting citizens’ interests. The article also highlights the significance of cooperation between state authorities and public organizations in achieving social stability and democratic development. In addition, the experience of modern democratic countries and the reforms carried out in Uzbekistan in the sphere of civil society development are considered. The research concludes that the effective interaction between the rule of law and civil society serves as the foundation for sustainable development, justice, and democratic progress.improvements in the workplace environment to ensure sustainable professional functioning.